Experimental study of drift eliminators in a spray filled tower - Mohiuddin, A. K. M. (2004)
The purpose of this paper is to determine the drift loss and pressure drop characteristics of cellular type drift eliminator and also those made of wood and cement-asbestos in a spray filled tower. The investigation were conducted with two and three stages of both wooden drift eliminators (WDE) and cement asbestos drift eliminators (CADE) with various orientation angle,  of the eliminator plates. The experiment was carried out with one, two and three stages for cellular type drift eliminators (CTDE). The results showed that the pressure drop and drift loss were strong functions of number of stages, n and air flow rate. In case of WDE and CADE, they were strongly dependent on orientation angle as well.